Ответ(ы) на вопрос:
[latex]-3 x^{3} +18 x^{2} +18x+6=0[/latex]
[latex] x^{3} -6 x^{2} -6x-2=0[/latex]
заменим x на [latex]y+ \frac{6}{3} [/latex]
[latex]x=y+2[/latex]
[latex] (y+2)^{3} -6 (y+2)^{2} -6 (y+2)-2=0[/latex]
[latex] y^{3} -18y-30=0[/latex]
пусть [latex]y=z+ \frac{6}{z} [/latex]
тогда после подстановки уравнение примет вид:
[latex] \frac{( z^{3}-18)(z^{3}-12)}{z^3}=0[/latex]
[latex]z= \sqrt[3]{18} [/latex][latex]z= \sqrt[3]{12} [/latex]
[latex]y= \sqrt[3]{18} + \frac{6}{\sqrt[3]{18}} [/latex]
[latex]y=\sqrt[3]{12} + \frac{6}{\sqrt[3]{12}} [/latex]
Получаем ответ:
[latex]x=\sqrt[3]{18} + \frac{6}{\sqrt[3]{18}} +2[/latex]
[latex]x=\sqrt[3]{12} + \frac{6}{\sqrt[3]{12}} +2[/latex]
Не нашли ответ?
Похожие вопросы